Effects of Syzygium aromaticum, Cinnamomum zeylanicum, and Salvia triloba extracts on proliferation and differentiation of dental pulp stem cells - Ayşegül Mendi; Beyza Gökçınar Yağci; Mustafa Kiziloğlu; Nurdan Saraç; Derviş Yilmaz; Aysel Uğur; Duygu Uçkan
Abstract Hypersensitivity, local irritative and cytotoxic effects are known for the chemical components of Syzygium aromaticum and Cinnamomum zeylanicum contained in dental materials. However, there is no intimate data in dentistry using the whole extracts of these plants and introducing new ones. Salvia triloba is a well-known anti-inflammatory plant that correspondingly could be used in several dental traumas. Objectives: We aimed to show and compare the effect of S. aromaticum, C. zeylanicum, and S. triloba extracts on dental pulp stem cells (DPSCs) proliferation, differentiation, and immune responses. Material and Methods: Using xCELLigence, a real time monitoring system, we obtained a growth curve of DPSCs with different concentrations of the Extracts. A dose of 10 μg/mL was the most efficient concentration for vitality. Osteogenic differentiation and anti-inflammatory activities were determined by using an ELISA Kit to detect early and late markers of differentiation. Results: The level of osteonectin (ON, early osteogenic marker) decreased, which indicated that the osteogenic differentiation may be accelerated with addition of extracts. However, the level of osteocalcin (OCN, late osteogenic marker and sign of calcium granulation) differed among the extracts, in which S. aromaticum presented the highest value, followed by S. triloba and C. zeylanicum. Surprisingly, the determined calcium granules were reduced in S. aromaticum and S. triloba. In response to tumor necrosis factor alpha (TNF-α), S. triloba-treated DPSCs showed the most reduced level of IL-6 cytokine level. We suggest C. zeylanicum as a promising osteogenic inducer and S. triloba as a potent anti-inflammatory agent, which could be used safely in biocomposite or scaffold fabrications for dentistry. Conclusions: Because calcium granule formation and cell viability play a critical role in hard tissue formation, S. aromaticum in dentistry should be strictly controlled, and the mechanism leading to reduced calcium granule formation should be identified.